Prevalence and associated factors of computer vision syndrome among the computer engineering students of Pokhara University affiliated colleges of Kathmandu valley - Sitaula, Kanchan; Kafle, Navaraj; Acharya, Aashish; Mishra, Ved Prakash (International Journal Of Community Medicine And Public Health, 2020)
Background: The increasing use of computers and electronic devices is rapidly increasing the related health issues of computer vision syndrome. Studies have identified longer use of computers, ergonomic practices as lighting condition of room, incorrect distance between eye and computer, refresh rate, use of spectacles were associated with computer vision syndrome (CVS) symptoms as back pain, tension, headache and others. The objective of this study was to find out the prevalence of CVS among computer engineering students of Pokhara University affiliated colleges of Kathmandu Valley and identify the associated factors and preventive measures being practiced by the students. Methods: A cross-sectional descriptive study was carried out using self-administered questionnaire among 234 undergraduate computer engineering students of Kathmandu Valley. Chi-square test was used to identify the association with computer vision syndrome and its determinants. Results: The prevalence of computer vision syndrome among the computer engineering students was found to be 76.50%. Only 39.3% were found to be using computer in upright with straight back posture and 73.5% were using computer at distance less than or equal to 50 cm. The 81.2% of participants were not following the 20/20/20 rule. During age, use of vision aid lens and use of protective eye glasses and artificial eye drops were found associated with CVS. Conclusions:The study revealed that the prevalence of computer vision syndrome was significantly high. Individuals using vision aid lens were found to be at risk of developing CVS and use of protective eye glass and artificial tears were found protective.